Role of TolR N-Terminal, Central, and C-Terminal Domains in Dimerization and Interaction with TolA and TolQ - Journet, Laure (American Society for Microbiology, 1999)
The Tol-PAL system of Escherichia coli is a multiprotein system involved in maintaining the cell envelope integrity and is necessary for the import of some colicins and phage DNA into the bacterium. It is organized into two complexes, one near the outer membrane between TolB and PAL and one in the cytoplasmic membrane between TolA, TolQ, and TolR. In the cytoplasmic membrane, all of the Tol proteins have been shown to interact with each other. Cross-linking experiments have shown that the TolA transmembrane domain interacts with TolQ and TolR. Suppressor mutant analyses have localized the TolQ-TolA interaction to the first transmembrane domain of TolQ and have shown that the third transmembrane domain of TolQ interacts with the transmembrane domain of TolR. To get insights on the composition of the cytoplasmic membrane complex and its possible contacts with the outer membrane complex, we focused our attention on TolR. Cross-linking and immunoprecipitation experiments allowed the identification of Tol proteins interacting with TolR. The interactions of TolR with TolA and TolQ were confirmed, TolR was shown to dimerize, and the resulting dimer was shown to interact with TolQ. Deletion mutants of TolR were constructed, and they allowed us to determine the TolR domains involved in each interaction. The TolR transmembrane domain was shown to be involved in the TolA-TolR and TolQ-TolR interactions, while TolR central and C-terminal domains appeared to be involved in TolR dimerization. The role of the TolR C-terminal domain in the TolA-TolR interaction and its association with the membranes was also demonstrated. Furthermore, phenotypic studies clearly showed that the three TolR domains (N terminal, central, and C terminal) and the level of TolR production are important for colicin A import and for the maintenance of cell envelope integrity.